Anorexia nervosa and gender dysphoria in two adolescents. Issue 1 (25th November 2014) - Couturier, Jennifer; Pindiprolu, Bharadwaj; Findlay, Sheri; Johnson, Natasha
ABSTRACT Little has been published about the co‐occurrence of gender dysphoria (GD) and eating disorders (ED) in adults, with no cases described in the adolescent population. The emphasis on body shape in both conditions suggests that there may be some overlap in symptomatology. We report two adolescent cases initially diagnosed with anorexia nervosa who later met criteria for GD. The drive for thinness for the 16‐year‐old male was associated with a wish to achieve a feminine physique whereas there was an emphasis for stunted breast growth and a desire for muscularity in the 13‐year‐old female. Complexities in presentation, evolution of symptoms over time, and the treatment of the two cases are discussed. Clinicians should inquire about sexual issues in the presentation of ED and should monitor for symptoms of GD, not only at initial presentation, but throughout treatment, especially as weight gain progresses. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:151–155)